Assessing the in vivo ameliorative effects of Lactobacillus acidophilus KLDS1.0901 for induced non-alcoholic fatty liver disease treatment - Wang, Yanbo; Wang, Zengbo; Wan, Yang; Jin, Furong; Shi, Xiaodan; Xing, Zhishuang; Tian, Bo; Li, Bailiang (Frontiers in Nutrition, 2023)
Reputed as a significant metabolic disorder, non-alcoholic fatty liver disease (NAFLD) is characterized by high fat deposits in the liver and causes substantial economic challenges to any country's workforce. Previous studies have indicated that some lactic acid bacteria may effectively prevent or treat NAFLD. In our previous study, L. acidophilus KLDS1.0901 could prevent chronic alcoholic liver injury and type 2 diabetes in mice by protecting the intestinal barrier and regulating gut microbiota. Thus, we hypothesized that L. acidophilus KLDS1.0901 would possess the ability to alleviate NAFLD. This study aimed to assess the protective effects of L. acidophilus KLDS1.0901 on high-fat diet(HFD)-induced NAFLD. Firstly, hepatic lipid profile and histological alterations were determined to study whether L. acidophilus KLDS1.0901 could ameliorate NAFLD. Then, the intestinal permeability and gut barrier were explored. Finally, gut microbiota was analyzed to elucidate the mechanism from the insights of the gut-liver axis. The results showed that Lactobacillus KLDS1.0901 administration significantly decreased body weight, Lee's index body, fat rate and liver index. L. acidophilus KLDS1.0901 administration significantly improved lipid profiles by decreasing the hepatic levels of total cholesterol (TC), triglyceride (TG), and low-density lipoprotein cholesterol (LDL-C) and increasing the high-density lipoprotein cholesterol (HDL-C) levels. A conspicuous decrease of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) in serum was observed after L. acidophilus KLDS1.0901 administration. Meanwhile, the H&E and Oil Red O-stained staining showed that L. acidophilus KLDS1.0901 significantly reduced liver lipid accumulation of HFD-fed mice by decreasing the NAS score and lipid area per total area. Our results showed that L. acidophilus KLDS1.0901 administration decreased the interleukin-6 (IL-6), interleukin-1β (IL-1β) and tumor necrosis factor-alpha (TNF-α) concentrations accompanied by the increase of interleukin-10 (IL-10). L. acidophilus KLDS1.0901 administration improves the intestinal barrier function by up-regulating the mRNA levels of Occludin. Claudin-1, ZO-1 and Muc-2, coupled to the decreases of the concentration of LPS and D-lactic acid. Notably, L. acidophilus KLDS1.0901 administration modulated the gut microbiota to near normal pattern. Hence, our results suggested that L. acidophilus KLDS1.0901 can be used as a candidate to ameliorate NAFLD.